A Description of English Teaching Based on Merdeka Curriculum at SMP N 1 Gorontalo - Pontoh, Meylan; Jusuf, Harni; Akhmad, Enni (English Education Department, 2024)
This study aims to describe the implementation of teaching English based on the Merdeka curriculum at SMPN 1 Gorontalo. It answers those questions, namely curriculum structure, learning achievement, learning and assessment, use of teaching devices. This research used descriptive qualitative method by using observation sheets, unstructured interview. It also documented RPS, lesson material, and students’ assignment. The data was analyzed through data reduction, data display, and data conclusion. The results of this study showed that the implementation of Merdeka curriculum in teaching English at SMPN 1 Gorontalo was in accordance with the provisions or regulations contained in the Decree of the Minister of Education, Culture, Research and Technology Republic of Indonesia number 262/M/2022.